Effects of armed conflict on economic growth in sub- Saharan Africa - Edokat, Edward Tafah; Ngongang, Elie; Zeh, Steve Rodrigue Akoumba (Eximia, 2023)
The empirical literature on the relationship between armed conflict and economic growth has been sparsely explored. Thus, the aim of this paper is to fill this gap in the literature by analysing the effects of armed conflict on economic growth by focusing on a sample of 16 Sub-Saharan African countries over the period 1984-2016. To do so, we use four indicators of conflict, namely: internal conflict, external conflict, ethnic tensions and religious tensions. In addition to these variables, we construct a synthetic conflict indicator using the PCA (Principal Component Analysis) method. The results obtained from the double least squares technique, which takes into account endogeneity problems, show that armed conflicts negatively affect economic growth in Sub-Saharan Africa. Also, these results remain robust to the addition of control variables and the use of alternative conflict indicators. However, we have also shown that a high level of economic growth can drive conflict to some extent in sub-Saharan African countries. From the same perspective, this has important policy implications.